2019
DOI: 10.2147/ott.s191519
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nab-paclitaxel in pretreated metastatic breast cancer: evaluation of activity, safety, and quality of life</p>

Abstract: Objective Metastatic breast cancer (MBC) is an incurable disease; the treatment of this disease prolongs survival, improving the quality of life (QoL) with a balance between efficacy and toxicity of the treatment. In recent years, treatment with nab-paclitaxel has improved the already known antitumor activity of conventional paclitaxel, in terms of increased efficacy and better tolerability. The aim of this study was to evaluate nab-paclitaxel in Italian patients with MBC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The improved drug delivery system increases intratumoral concentrations while shielding normal, healthy cells from drug toxicities. Clinical trials have shown success with nab-PTX in metastatic breast and pancreatic cancer [ 11 , 12 ], though more research should be done on potential benefits in other cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…The improved drug delivery system increases intratumoral concentrations while shielding normal, healthy cells from drug toxicities. Clinical trials have shown success with nab-PTX in metastatic breast and pancreatic cancer [ 11 , 12 ], though more research should be done on potential benefits in other cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…And metastatic breast cancer by definition is incurable. 7 Our study showed 30% of patients presenting with metastatic disease at the time of the diagnosis whilst 34% had locally advanced disease. Soomro et al 5 retrospectively looked into 10,018 breast cancer patients in a tertiary care center in Karachi Pakistan and reported 28% of patients to have metastatic disease at presentation which is comparable to our study.…”
Section: Discussionmentioning
confidence: 54%
“…Other ionic and block copolymer-based drug modifications are still under study. An albumin-bound paclitaxel, abraxane, has already received FDA approval for treatment of metastatic breast cancers (88). Opaxio/Xyotax, a poly-L-glutamic acid-paclitaxel, is currently under Phase III clinical trials for the treatment of ovarian and esophageal cancers (89).…”
Section: P-gp Substrate and Drug Interactionsmentioning
confidence: 99%